Nursing civil rights : gender and race in the Army Nurse Corps - Threat, Charissa J., 1976- (Women in American history., 2015)
In 'Nursing Civil Rights', Charissa J. Threat investigates the parallel battles against occupational segregation by African American women and white men in the U.S. Army. As Threat reveals, both groups viewed their circumstances with the Army Nurse Corps as a civil rights matter.